EFFICIENCY OF USING ASSET AND FINANCIAL PERFORMANCE: THE CASE OF INDONESIA MANUFAKCTURING COMPANIES - Miswanto Miswanto; Diczon Stevanus Oematan (Universitas Mercu Buana, 2020)
This study analyzes the impact of asset use efficiency on financial performance and the impact of financial performance on shareholders' wealth. By using a research sample of manufacturing firms listed on the Indonesia Stock Exchange (IDX), the purpose of this study is to test whether: 1) the efficiency of using asset has a positive impact on financial performance and 2) financial performance has a positive impact on the welfare of shareholders. The analytical method uses SEM (Structural Equation Model) –(PLS (Partial Least Square) using WarpPLS 5.0. The asset efficiency variable is measured by activity ratios and the shareholder wealth variable is measured by stock return and firm value. The analytical techniques that used are outer model and inner model analysis. The variables of asset efficiency and shareholder wealth are measured variables and the financial performance variable is latent variable. The proceeds of his study state that the activity ratio: 1) working capital turnover (WCT), receivable turnover RCT), inventory turnover (INT), total asset turnover (TAT) have a positive impact on financial performance, and 2) cycle of cash conversion (CCC) has a negative impact on financial performance. The results of this study also states that financial performance positive impact on stock return and firm value. Thus, this study finds that the efficiency of using asset has a positive impact on financial performance, and performance of financial has a positive impact on stockholder wealth